Correction to: Relational continuity with primary and secondary care doctors: a qualitative study of perceptions of users of the Catalan national health system - Sina Waibel; Ingrid Vargas; Jordi Coderch; María-Luisa Vázquez (BMC, 2018)
Following publication of the original article [1], the authors reported a correction in affiliation of Maria Luisa Vázquez, who is affiliated with Health Policy and Health Services Research Group, which is number 1 instead of being affiliated with Grup de Recerca en Serveis Sanitaris i Resultats en Salut, Serveis de Salut Integrats Baix Empordà, Carrer Hospital 17-19 Edifici Fleming, 17,230 Palamós, Spain.